MAHASISWA DAN HAFALAN AL-QUR’AN (Studi Living Qur’an Tentang Pemahaman Mahasiswa IQT 2017 Terhadap Surah Al-Hijr Ayat 9 dan Motivasi Dalam Menghafal Al-Qur’an) - Anggi Mustika Dewi Listyawati; Pathur Rahman; Anggi Wahyu Ari (Program Studi Ilmu Al quran dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2022)
This research started from the study program of Al-Qur'an and Tafsir, namely a department that directs students to memorize the Qur'an in each semester by memorizing one juz for four consecutive semesters. However, many of these students did not finish their memorization when they met the tahfiz course. While in the Qur'an there is a verse that becomes a motivation in memorizing the Qur'an, the verse is contained in Surah Al-Hijr verse 9. The data collection procedure used observation, interviews and documentation. The results showed that the subject understood that Surah Al-Hijr verse 9 was a motivational verse in memorizing the Qur'an. Then the reason that makes the students do not complete their memorization, because they experience obstacles when memorizing the Qur'an such as not being able to read the Qur'an properly, the emergence of a feeling of laziness from within them can cause feelings of boredom, despair and loss of enthusiasm in memorizing the Qur'an, not being able to properly divide time between lectures and memorizing the Qur'an, and the last one is caused by environmental factors that are not appropriate for memorizing the Qur'an. The motivations possessed by students in memorizing the Qur'an are: wanting to make their parents happy and uplifting, in order to get glory in this world and the hereafter, seeking the pleasure of Allah Swt and the most important motivation is wanting to obey the rules of the IQT study program because it requires memorize the Qur'an.